1984
DOI: 10.3354/meps014111
|View full text |Cite
|
Sign up to set email alerts
|

Vertical distribution and partitioning of organic carbon in mixed, frontal and stratified waters of the English Cannel

Abstract: The vertical distribution of plankton is described for 3 stations representative of stratified. frontal and vertically mixed regions of the western English Channel in summer. All components of organic carbon, representing dissolved and particulate organic carbon, phytoplankton, bacteria. protozoans, micro-and meso-zooplankton, were estimated independently. Major differences were found In the abundance and species composition of the phytoplankton, and in the relative proportions of different groups of heterotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
111
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(122 citation statements)
references
References 26 publications
11
111
0
Order By: Relevance
“…In this study, assuming a cell carbon content of 13 pg (Holligan et al, 1984), the observed cellular POC levels of E. huxleyi cells in the blooming area were similar, with a range of 13-40 ”g C dm 3 and equivalent to 6.4-19.7% of the total community POC. In mesocosm experiments, the amount of particulate organic carbon in living cells of E. huxleyi may be as much as 500 ”g dm 3 (Van Bleijswijk et al, 1994).…”
Section: The State Of Development Of the Bloommentioning
confidence: 91%
“…In this study, assuming a cell carbon content of 13 pg (Holligan et al, 1984), the observed cellular POC levels of E. huxleyi cells in the blooming area were similar, with a range of 13-40 ”g C dm 3 and equivalent to 6.4-19.7% of the total community POC. In mesocosm experiments, the amount of particulate organic carbon in living cells of E. huxleyi may be as much as 500 ”g dm 3 (Van Bleijswijk et al, 1994).…”
Section: The State Of Development Of the Bloommentioning
confidence: 91%
“…Biomass for (B] to (D] from Holligan et al (1984) solution, either temporarily or permanently. The surprising thing about the comparisons made above between calculated and observed rates of viral disappearance is how well the mass transport estimates agree with the measurements, suggesting that transport to particle surfaces is a fundamental part of viral inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Holligan et al 1984). Observed biomass levels for organisms between 2 and 90 pm diameter in surface waters of the English Channel vary with hydrographic conditions (Fig.…”
Section: Calculated Host:virus Contact Rates For Particle Distributionsmentioning
confidence: 99%
“…In the middle shelf domain, a chlorophyll maximum can persist in the pycnocline into the fall (Iverson et al, 1979a;Stockwell et al, 2001), implying that new production continues in this subsurface layer, as on other continental shelves (Holligan et al, 1984;Richardson and Christoffersen, 1991). Mixing events from summer storms provide the only nutrient enrichment of surface waters on the middle and outer shelf (Whitledge et al, 1986;Sambroto et al, 1986).…”
Section: Study Areamentioning
confidence: 99%